The future of soil carbon : its conservation and formation - Garcia, Carlos; Nannipieri, Paolo; Hernandez, Teresa (Elsevier Ltd. : Academic Press, 2018)
The Future of Soil Carbon: Its Conservation and Formation provides readers with an integrative approach to understanding the important role of organic carbon in soil functioning and fertility. Terrestrial interactions between SOC and complex human-natural systems require new fundamental and applied research into regional and global SOC budgets. This book provides new and synthesized information on the dynamics of SOC in the terrestrial environment. In addition to rigorous state-of-the art on soil science, the book also provides strategies to avoid risks of soil carbon losses. Soil organic carbon (SOC) is a vital component of soils, with important and far-reaching effects on the functioning of terrestrial ecosystems. Human activities over the last several decades have significantly changed the regional and global balance of SOC, greatly exacerbating global warming and climate change. Provides a holistic overview of soil carbon status and main threats for its conservation Offers innovative solutions to conserve soil carbon Includes in-depth treatment of regional and global changes in soil organic carbon budget.